Easing the Anxiety Crescendo: How Structured Listening Comprehension Influences Mental Health in Music Students - Triyono Bramantyo; Chow Ow Wei; Sagaf Faozata Adzkia (Harmonia: Journal of Arts Research and Education, 2026)
This study investigated whether structured listening comprehension activities reduce performance anxiety among undergraduate music students. Sixty participants completed four weeks of guided listening sessions focused on classical, jazz, or popular music combined with reflective prompts encouraging emotional interpretation and cognitive engagement. A quasi-experimental pretest-posttest design employed the State-Trait Anxiety Inventory and qualitative reflections to evaluate outcomes. Anxiety levels declined across all groups, with the greatest reduction observed in the classical music condition, followed by jazz and popular music. Findings indicate that reflective listening processes, including attention, interpretation, and emotional awareness, may help reduce anxiety and enhance psychological well-being in music education.